A Vitrine e o Lumpen: práticas e apropriações do espaço público de coletivos de arte, política e cultura lumpen em Fortaleza - Fragoso, Tiago de Oliveira (2018)
This work is a research on the practices of occupation of the public space by members of a political, cultural and lumpen organization, the Hip Hop Force, in Fortaleza. It seeks to understand the construction of the meanings that shape the urban experience of these agents in the city of Fortaleza, mediated by their artistic activities and urban social events. In order to establish an adequate understanding of the way public space is occupied by cultural activities, a comparison will be made between the hip hop events organized in Dragão do Mar and the cultural events organized by the Hip Hop Force in peripheral spaces of the city. This comparison allowed a comprehensive approximation of the complexity that exists between occupation of space, political and cultural struggle and commercialization of culture. The meetings of the break dancers that take place in the space below the planetarium Rubens de Azevedo at the Dragão do Mar Cultural Center seem to be the "showcase" of break / hip hop in Fortaleza, in the view of the practitioners themselves. The break dancers for a few hours become one of the cultural products arranged and consumed by the public. This "showcase" of hip hop can be put into perspective in relation to other cultural occupations in the city. From the "other side" of the city are organized in neighborhood squares abandoned by the public power, cultural events with characteristics similar to those made in the Dragon of the Sea. These events have as distinctive characteristic the fact that they are done almost in an improvised way, without great resources , articulated spontaneously through social networks and linked to political and cultural patterns of the periphery. These events are called "lumpen" by members of cultural collectives associated with the Hip Hop Force. This research is, therefore, an understanding of the way in which this "lumpen" occupation of the city space occurs, outside of the mainstream cultural circuits of the city of Fortaleza.